Making Sense of Single‐Case Design Effect Sizes. Issue 3 (1st July 2019) - Maggin, Daniel M.; Cook, Bryan G.; Cook, Lysandra
Abstract: Single‐case research methods provide a basis for demonstrating that an intervention produces a reliable change in a targeted outcome for individual cases. To supplement visual analysis of data in single‐case studies, researchers frequently report statistics—often referred to as effect sizes—to summarize study findings. The recent proliferation of effect sizes used in single‐case research can be confusing. In this article, after reviewing single‐case research, we provide an overview of common types of effect sizes used in single‐case research, including overlap metrics and within‐ and between‐participant effect sizes, and conclude with examples of these effect sizes in the single‐case literature. Our take‐home message is that effect sizes are useful complements to visual analysis when interpreting results of single‐case design research studies.